Climate-Induced Migrants, International Law, and Human Rights, an Assessment - Ali, Abdikarim (Université d'Ottawa | University of Ottawa, 2015)
As the planet’s ocean and seawaters continue to rise, coastal land becomes inundated, staple crops are destroyed by salinity intrusion, ecosystems are decimated or altered due to salt toxicity, and human populations are forcibly displaced. The resulting displaced persons, safely referred to as climate-induced migrants, either become internally displaced persons (IDP’s) within their borders or cross international borders as a means of survival. Legally these migrants fall outside the rigid framework of the International Legal Regime for the protection of refugees. Unfortunately the plight of these climate-induced migrants is not aligned with the scope and definition of the 1951 United Nations Convention on the Status of Refugees and the 1967 Protocol Relating to the Status of Refugees. On the international political stage, state actors continue to block any tangible attempts to politically recognize and address the issue of climate-induced migration, which is often directly associated with emissions reduction obligations by the Global South. Despite the political aversion to fully accepting and addressing climate induced migration, up to an including the re-assessment of the definition of a refugee, the international community continues to discuss the question of migration and climate change. On the agenda of the United Nations Framework Convention on Climate Change (UNFCC) and other related meetings occurring on the margins of the UNFCCC’s Conference of Parties (CoP) discussions, is the issue of climate change and migration. In light of this growing political momentum and the willingness of key stakeholders to discuss climate change and migration, this paper will aim to determine potential opportunities the international community and key stakeholders can pursue, in order to develop lasting solutions on the issue of climate change and migration, while assessing the need for greater international legal protection for climate-induced migrants, and more robust climate change adaption assistance for their home states.